2009
DOI: 10.1007/s10573-009-0092-7
|View full text |Cite
|
Sign up to set email alerts
|

Detonation characteristics of powerful insensitive explosives

Abstract: Experimental and calculated detonation characteristics of powerful insensitive explosives are given. Features of explosives with a high hydrogen content are discussed. The relationship between the power and sensitivity characteristics of explosives and the structure of their molecules are considered. Prospects for the development of powerful explosives are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…13. Most likely, these data were obtained at low temperatures, since a later X‐ray study at ambient temperature reported the crystal density of 1.875 g cm −3 5. In Refs.…”
Section: Introductionmentioning
confidence: 97%
“…13. Most likely, these data were obtained at low temperatures, since a later X‐ray study at ambient temperature reported the crystal density of 1.875 g cm −3 5. In Refs.…”
Section: Introductionmentioning
confidence: 97%
“… In the azaisowurtzitanes derivatives their reactivity and performance increases from left to right (mutually confer data from Refs. 2–5 and from this paper; Auroras 5 and 6 are mutually different only by stability 1,3). …”
Section: Introductionmentioning
confidence: 49%
“…The more distinctly negative oxygen balance of Aurora‐5 and TEX causes the fact that their data do not correlate with those of RDX, HMX, and BCHMX. TEX is proposed for use as a LOVA explosive 5.…”
Section: Resultsmentioning
confidence: 99%
“…The performance of an explosive is appreciated by its detonation velocity (D) and detonation pressure (P CJ ) [21,22], and for a propellant by its specific impulse (I SP ) [23,24]. These parameters are determined by the oxygen coefficient (α), enthalpy of formation (∆H f ), and density (ρ).…”
Section: Introductionmentioning
confidence: 99%